107k views
3 votes
(4a-7)^2 simplify in detail

User Kurt Telep
by
5.4k points

2 Answers

5 votes

Answer:

16a^2 - 56a + 49

Explanation:

(4a - 7)(4a-7)

4a(4a - 7) - 7(4a - 7)

16a^2 - 28a - 28a + 49

16a^2 - 56a + 49

User Nadir Latif
by
5.4k points
1 vote

Explanation:


= (4a - 7 {)}^(2) \\ = (4a {)}^(2) - 2 * 4a * 7 + {7}^(2) \\ = 16 {a}^(2) - 56a + 49

Here we used the formula,


(a - b {)}^(2) = {a}^(2) - 2ab + {b}^(2)

Here, 4a=a and 7=b.

Sustitute the value in the formula and simplfy.

User Mhesabi
by
5.0k points